Efficient System of Laser Diode CW Pumped on Nd:YAG Laser - F. H. Mustafa; M. I. Azzawe (College of Education for Pure Sciences, 2008)
Abstract In this paper, we report the recent progress made in the design and development of a miniature solid-state system, consisting from a bar laser diode and a slab of Nd:YAG crystal. Single longitudinal mode, stable CW power output at 1064 nm wavelength has been demonstrated. An ever power conversion efficiency was reached with an amount of 46.32%. Bar laser diode of wavelength 803 nm, and power output up to 24 W was used as a direct pumping device. Basic principles of operation and output characteristics will be demonstrated by this proposed technique. Taking the full advantages of the bar laser diode array, influencing the mechanisms of excitation, amplification, and saturation in the crystal; spectral emission, efficiency and beam quality can be tailored in the experiment.